Casebook for a Spiritual Strategy in Counseling and Psychotherapy. 2004
DOI: 10.1037/10652-012
|View full text |Cite
|
Sign up to set email alerts
|

Humanistic integrative spiritual psychotherapy with a Sufi convert.

Abstract: I am a White man, and I have been a member of the Religious Society of Friends (Quakers) since December 1992. Prior to that, I was a member of the Church of England, but I more or less gave up church membership when I enrolled in a university at the age of 18. However, I retained a keen interest in spirituality. I regard myself as fairly devout, attending Quaker Meetings for Worship every Sunday with my wife and child whenever possible, and I have served as an Elder of my previous Quaker meeting while living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Spiritual interventions are being used with increasing frequency across all types of treatment, including, individual therapy (Richards & Bergin, 2003), group therapy (Hiatt, 1999), marriage and family therapy (Butler & Harper, 1994), and child and adolescent therapy (Miller, 2004). Spiritual perspectives and interventions have now been incorporated into most mainstream theoretical orientations, including, the psychoanalytic tradition (Shafranske, 2004), Adlerian therapy (Watts, 2000), behavior therapy (Martin & Booth, 1999), cognitive therapy (Propst, 1996), rational-emotive behavior therapy (Nielson, Johnson & Ellis, 2001), person-centered therapy (West, 2004), existential-humanistic therapy (Mahrer, 1996), Gestalt therapy (Harris, 2000), constructivism (Steinfeld, 2000) and transactional analysis (Trautmann, 2003). Religion and spirituality are also increasingly seen as important aspects of client diversity, with spiritual perspectives and interventions being incorporated into treatment with various multicultural and special client populations (e.g.…”
Section: Spiritual Approachesmentioning
confidence: 99%
“…Spiritual interventions are being used with increasing frequency across all types of treatment, including, individual therapy (Richards & Bergin, 2003), group therapy (Hiatt, 1999), marriage and family therapy (Butler & Harper, 1994), and child and adolescent therapy (Miller, 2004). Spiritual perspectives and interventions have now been incorporated into most mainstream theoretical orientations, including, the psychoanalytic tradition (Shafranske, 2004), Adlerian therapy (Watts, 2000), behavior therapy (Martin & Booth, 1999), cognitive therapy (Propst, 1996), rational-emotive behavior therapy (Nielson, Johnson & Ellis, 2001), person-centered therapy (West, 2004), existential-humanistic therapy (Mahrer, 1996), Gestalt therapy (Harris, 2000), constructivism (Steinfeld, 2000) and transactional analysis (Trautmann, 2003). Religion and spirituality are also increasingly seen as important aspects of client diversity, with spiritual perspectives and interventions being incorporated into treatment with various multicultural and special client populations (e.g.…”
Section: Spiritual Approachesmentioning
confidence: 99%
“…Sufi spirituality can help the healing process after trauma by enhancing personal growth and giving a positive meaning to suffering that enhances growth and resilience in trauma situation ( Joseph, 2009). The Sufi master (or teacher) can also play a role in meeting the client's developmental need in dealing with traumatic events that prevent growth (West, 2004). Hipolito et al (2014) concluded from their study that incorporating spirituality in trauma treatment programs enabled trauma-informed services to treat clients with the empowerment that spirituality gives to trauma sufferers.…”
Section: Using Spirituality As An Element In Traumamentioning
confidence: 99%
“…Sufism is therefore the transcending of ordinary limitation. (p. 14) Shah's description of the benefits of mental experiences to Sufis has been associated with the self-growth and personal development experienced on the Sufi path (West, 2004). The possible role of Sufism and other mystical traditions can be of "transformational intensity" when combined with modern psychotherapeutic methods (Nixon & Zangeneh, 2012).…”
Section: The Way Forward In Integrating Emdr With the Sufi Dhikrmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Miller, 1999; Richards & Bergin, 2000, 2005; Sperry & Shafranske, 2005). For example, scholars have integrated theism with psychodynamic therapy (Shafranske, 2004), rational emotive behavior therapy (Nielsen, Johnson, & Ellis, 2001), integrative therapy (Sperry, 2004), humanistic therapy (West, 2004), interpersonal therapy (Miller, 2004), and others. Although much progress has been made in integrating spirituality into mainstream psychotherapy, sometimes these integrative approaches lack consistency among their theological, philosophical, and practical levels.…”
mentioning
confidence: 99%